Components of the Profitability of Technical Currency Trading - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2005)
This paper investigates the sources of the profitability of 1024 moving average and momentum models when trading in the German mark (euro)/U.S. dollar market based on daily data. The main results are as follows. First, each of these models would have been profitable over the entire sample period. Second, this profitability is exclusively due to the exploitation of persistent exchange rate trends. Third, these results do not change substantially when trading is examined within subperiods. Fourth, the 25 best performing models in each in-sample period examined were profitable also out of sample in most cases. Fifth, the profitability of technical trading the German mark (euro)/U. S. dollar exchange rate has been significantly lower since the late 1980s as compared to the first 15 years of the floating rate period.
Keywords: F31; G14; G15; 330; Exchange rate; Technical trading; Währungsspekulation; Deutsche Mark; US-Dollar; Informationseffizienz; Schätzung